MITIGASI REAKSI ALKALI SILIKA (ASR) DENGAN MENGGUNAKAN ABU TERBANG (FA), SILICA FUME (SF), DAN BUBUK PERLITE DIPERLUAS (BP) - M Isneini 1 (Balitbangda Provinsi Lampung, 2020)
Abstract: Reduction of ASR by FA, ​​SF, BP, evaluated using concrete prisms and mortar bars. Concrete prisms were casted in accordance with RILEM AAR-3, while mortar bars were made according to JIS A 1146. Both specimens were stored in the control room 40oC 100% R.H. Mixture of concrete and mortar using aggregate in pessimum proportions. The test results show that the effectiveness of FA at the level of 25%, SF10%, and BP10% can reduce expansion. Concrete pore size distribution with FA, SF, and BP looks better than control concrete. UPV results using FA25 and SF10 tend to be higher compared to other mixtures. Keywords: ASR, mineral, mitigation, pessimum proportion, single